Proportional incidence of interval colorectal cancer in a large population-based faecal immunochemical test screening programme. Issue 4 (April 2020) - Mancini, Silvia; Bucchi, Lauro; Giuliani, Orietta; Ravaioli, Alessandra; Vattiato, Rosa; Baldacchini, Flavia; Ferretti, Stefano; Sassoli de Bianchi, Priscilla; Mezzetti, Francesca; Triossi, Omero; Serafini, Monica; Ricci, Enrico; et al.
Abstract: Background: The European guidelines for quality assurance in colorectal cancer (CRC) screening recommend that interval cancer rate be expressed as a proportion of background incidence rate. Aim: To determine the crude and adjusted proportional incidence of interval CRC in an Italian regional two-yearly faecal immunochemical test (FIT) screening programme. Methods: The programme (year of implementation, 2005) is targeted at over 1, 000, 000 people aged 50–69 years. The test is a one-sample OC-Sensor (Eiken Chemical Co., Tokyo, Japan). The study covered one-third of the regional area. Excerpts of 434, 295 eligible negative FIT records dated 2005–2012 from 193, 193 subjects were retrieved from the regional CRC screening data warehouse. By 31 December 2013, the cohort accumulated 198, 302 man-years and 235, 370 woman-years. Interval CRCs were identified by record-linkage with the local population-based cancer registry. Their number was divided by the expected number, estimated with age-period-cohort models, to obtain the proportional incidence. Results: The proportional incidence of interval CRC for men and women was, respectively, 0.06 (95% confidence interval (CI), 0.04–0.09) and 0.17 (95% CI, 0.13–0.23) in the first interval year, and 0.21 (95% CI, 0.16–0.26) and 0.28 (95% CI, 0.22–0.36) in the second year. Conclusions: The results were acceptable and in line with previous studies.